USE OF MIXED TECHNOLOGIES IN PUBLIC EDUCATION ADMINISTRATION (Innovative professional education, 2024)
The problematic aspects of the adaptation of teaching staff to mixed technologies in public education administration are investigated. The models of mixed technologies in public education administration are identified and analysed. Attention is focused on the problems that teachers and administrators face when using innovative technologies and promising vectors for further implementation of mixed technologies in public educationadministration.
Keywords: Blended learning technologies, public administration of education, adaptation